The Role of Virtual Reality in Enhancing Skill-Based Training Programs - Lan, Tạ Thị; Nhựt, Võ Minh; Long, Hà Bảo (International Journal of Technology and Modeling, 2024)
Virtual Reality (VR) technology has emerged as a promising tool to revolutionize skill-based training programs by providing immersive and interactive learning environments. This study explores the impact of VR on enhancing training effectiveness within Vietnam’s workforce development initiatives. Through a mixed-methods approach combining quantitative performance data and qualitative feedback from 300 trainees across manufacturing, healthcare, and vocational education sectors, the research evaluates VR’s role in improving skill acquisition, learner engagement, and retention compared to traditional training methods. The findings indicate that VR-based training significantly increases post-training proficiency scores by an average of 25%, while reducing the time required to achieve competency by approximately 30%. In manufacturing, VR simulations enable trainees to safely practice assembly line operations and error management, resulting in fewer workplace mistakes. In healthcare, VR modules focused on surgical and procedural training improve procedural confidence and adherence to clinical protocols. User surveys reveal high satisfaction levels, particularly appreciating the realistic, risk-free practice environment. However, challenges such as high initial investment costs, limited localized VR content, and technical infrastructure gaps—especially in rural areas—limit widespread adoption. Addressing these barriers requires targeted strategies including content localization, government support, and infrastructure development. This study underscores VR’s potential to enhance skill-based training effectiveness and accelerate workforce readiness in emerging economies like Vietnam. It provides critical insights for policymakers, educators, and industry leaders aiming to integrate advanced technologies into training programs to meet evolving labor market demands.